Selection of putative Terra Maranhão plantain cultivar mutants obtained by gamma radiation - Reis, R.V.; Amorim, E.P.; Ledo, C.A.S.; Pestana, R.K.N.; Gonçalves, Z.S.; Borém, A. (Genetics and Molecular Biology, 2015)
The aim of this study was to select putative Terra Maranhão plantain cultivar mutants obtained by gamma radiation, with good agronomic traits and short height. A total of 315 buds were irradiated in vitro with gamma rays in doses of 20 Gy and were subcultivated and evaluated in the field over 2 production cycles. The clones were evaluated to select the best 10% of the plants. Cultivation was undertaken at a spacing of 3 x 4 m, and fertilization was carried out according to the technical recommendations for the crop. A total of 111 irradiated plants and 41 controls were evaluated in the field. Among the irradiated plants selected, genotypes that exhibited reduced height were observed. The genotypes Irra 04, Irra 13, Irra 19, and Irra 21 exhibited a height of 3.6 m, which was below the mean value of the controls selected. Other irradiated genotypes selected such as Irra 14 and Irra 16, with a height of 3.65 m, are promising because, in addition to reduced height, they exhibited good bunch weight and shorter period to flowering in relation to the mean value of the controls, which is a significant factor for the next stages in breeding. These results confirm the possibility of inducing mutations in Terra type banana plants to obtain desirable agronomic traits and short height.
Keywords: Musa spp; Short plant stature; Selection of mutants